EVALUATION OF HIGHER EDUCATION LEARNING MANAGEMENT SYSTEM USABILITY USING SYSTEM USABILITY SCALE - Atika Herawati; Muchlas Suseno; Siti Drivoka Sulistyaningrum (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
During pandemic COVID-19, higher education has made a large shift in turning synchronous learning into asynchronous learning through online learning platforms. It encourages every institution, likewise Universitas Negeri Jakarta, to provide an all-in-one technology-supported learning environment due to face this dynamic change. Therefore, UNJ has finally developed its own Learning Management System (LMS). However, since it is a new brand tool of learning and innovation, it needs to be quickly evaluated for satisfaction and optimization so that there can be proposed for improvements in the future. This research uses System Usability Scale (SUS) as the Usability evaluation methods which is distributed through Google Forms and measured the validity by SPSS software. This evaluation method has been done to 50 participants from undergraduate and graduate students of English Language Education Study Program at UNJ. It was found that the result was valid with 0,702 reliability rate. The evaluation result of LMS owned by UNJ has 83,25 SUS score which can be regarded as